The Secondary Traumatic Stress Scale: Confirmatory Factor Analyses With a National Sample of Victim Advocates. Issue 5 (March 2021) - Benuto, Lorraine T.; Yang, Yueran; Ahrendt, Andrew; Cummings, Caroline
Secondary traumatic stress (STS) is a pattern of psychological symptoms that approximates the symptoms of posttraumatic stress disorder (PTSD) and occurs in professionals who are exposed to individuals who have experienced trauma. While victim advocates are frontline health professionals who are trained to support victims of crime and interpersonal violence and are at risk for developing STS, they have been largely neglected in the extant literature on STS. The STS Scale (STSS) is a 17-item self-report questionnaire utilized to assess frequency of symptoms of intrusion, avoidance, and arousal, specifically related to providing services to victims of trauma. The purpose of this study was to investigate the psychometric properties of the STSS with a sample of victim advocates ( N = 135) using confirmatory factor analysis (CFA). Results indicated that both a single-factor model and three-factor model were equivalent. This study represents a first attempt to validate a measure of STS among victim advocates, a unique and understudied population who are at risk for developing STS given their work with individuals who have experienced interpersonal violence. Establishing effective, easy to administer, and efficient measures of STS is important given that this population encounters secondary trauma on a regular basis in the context of their job. While additional theoretical work regarding the construct of STS is needed, the STSS did demonstrate high reliability with this population and thus can be used as part of the assessment of STS among victim advocates.